PERANCANGAN COMMUNITY CENTER DI KOTA TANGERANG SELATAN DENGAN PENDEKATAN ARSITEKTUR BIOFILIK - Ammar Fadhilah; Anggraeni Dyah Sulistiowati; Karya Subagya (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
ABSTRACT The City of South Tangerang is a growing city, from an increasing population, as a result of immigrants or urban communities, which has led to the emergence of diverse communities. Therefore, as the population increases, the needs of the community are increasing, one of which, is a place like the Community Center. The Community Center is needed to accommodate and facilitate community and community activites. The Community Center learn about the understanding and basic knowledge, such as planning and designing requirements for the Community Center. In planning the construction of the Community Center, a comparative study has been carried out from several facilities similar to Community Center, which have built in several nearby cities and references in several countries. Designing the Community Center development, the author determines the site location has been chosen on Jl. Boulevard Bintaro Jaya, Segmen6, Parigi, Pondok Aren, Kota Tangerang Selatan, Banten. The design of the Community Center is related to the layout of the building and the space of the building, the appearance of the building using the materials, structures, and utilities in the design. The Community Center design concept, uses the concept of Biophilic Architecture. Biopihilic Architecture concept that, harmonizes people, buildings, and the environment. Therefore, according to the problems in South Tangerang City, because it is in the middle of another city that has more advanced city conditions, causing South Tangerang City to be affected, namely increasing pollution. In overcoming these problems, the concept of Biophilic Architecture is the Answer to existing problems, with involving humans, buildings and the environment, through use of visualization, plants, and water, as well as applying the principles of Biophilic Architecture to sites and buildings. The result will produces a place to live or a healthy environment and mentally, and physically for the surrounding community.